2019
DOI: 10.1053/j.gastro.2019.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinomas With Mutational Activation of Beta-Catenin Require Choline and Can Be Detected by Positron Emission Tomography

Abstract: Apc ko-liv mice, the methionine-and choline-deficient diet reduced proliferation and DNA hypermethylation of hepatocytes and HCC cells, and the CD diet reduced long-term progression of tumors. CONCLUSIONS: In mice and humans, HCCs with mutations that activate b-catenin are characterized by increased uptake of a fluorocholine tracer, but not 18 F-fluorodeoxyglucose, revealed by PET. The increased uptake of choline by HCCs promotes phospholipid formation, DNA hypermethylation, and hepatocyte proliferation. In mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 36 publications
2
36
0
1
Order By: Relevance
“…The phospholipid signatures that best discriminated HCC from non-tumor liver tissue in our study included several different species of phosphatidylcholines. PET imaging using 18 F-fluorocholine is an imaging biomarker of phosphotidylcholine synthesis that is currently used for clinical detection of HCC in some regions [43,44] It has been shown to be superior to PET imaging of glucose metabolism with 18 F-fluoro-deoxy-D-glucose (FDG) for the detection of HCC, implying that lipogenesis is more salient than glycolysis as a metabolic feature of HCC [43,45,46]. Other studies have identified lipogenic networks characterized by specific lipid metabolites as being associated with HCC progression and survival [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phospholipid signatures that best discriminated HCC from non-tumor liver tissue in our study included several different species of phosphatidylcholines. PET imaging using 18 F-fluorocholine is an imaging biomarker of phosphotidylcholine synthesis that is currently used for clinical detection of HCC in some regions [43,44] It has been shown to be superior to PET imaging of glucose metabolism with 18 F-fluoro-deoxy-D-glucose (FDG) for the detection of HCC, implying that lipogenesis is more salient than glycolysis as a metabolic feature of HCC [43,45,46]. Other studies have identified lipogenic networks characterized by specific lipid metabolites as being associated with HCC progression and survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified lipogenic networks characterized by specific lipid metabolites as being associated with HCC progression and survival [20]. The Wnt/beta-catenin pathway has been implicated in hepatocarcinogenesis [47], and mutations causing activation of beta-catenin have been associated with increased tumor phospholipid biosynthesis and uptake of 18 F-fluorocholine in HCC [44]. Beta-catenin activation has also been associated with increased fatty acid oxidation in HCC [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of β-catenin was involved in HCC progression. Additionally, CTNNB1 mutation was frequently detected in HCC tissues compared to those of adjacent liver (31). The data in this study identified NCSTN as the upstream regulator of βcatenin and promoted its nuclear translocation, thereby induced Zeb1-mediated EMT process, resulting in malignant phenotype.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, the focal activation of β-catenin in vivo in single murine hepatocytes is oncogenic, leading to the development of β-catenin-activated liver tumors ( Colnot et al, 2004 ). We used transcriptomic and metabolomic approaches and showed that the genetic program expressed in β-catenin-activated liver is similar to the oncogenic signature found in human HCC harboring activating β-catenin mutations ( Gougelet et al, 2014 ; Gougelet et al, 2019 ; Senni et al, 2019 ).…”
Section: Introductionmentioning
confidence: 96%